2013
DOI: 10.1177/0829573512468845
|View full text |Cite
|
Sign up to set email alerts
|

Disguised Distress in Children and Adolescents “Flying Under The Radar”

Abstract: It is now recognized that there is a very high prevalence of psychological disorders among children and adolescents and relatively few receive psychological treatment. In the current article, we present the argument that levels of distress and dysfunction among young people are substantially underestimated and the prevalence of psychological problems is higher than realized because of a variety of factors. In particular, it is suggested that psychological problems are underestimated due, in part, to the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 44 publications
0
26
0
5
Order By: Relevance
“…A US study by Merikangas and colleagues (2010) showed that 22.2% of 13-18 year olds met the clinical assessment criteria for severe impairment or distress (anxiety 31.9%, behavioural disorders 19.1%, mood disorders 14%). Adding further concern, Canadians Flett and Hewitt (2013) showed that mental health issues were generally underestimated, citing lack of disclosure, as well as a range of existing sub-threshold conditions not quite meeting criteria for diagnoses. Over the last century, increased urbanization populations have experienced a general trend of increased life expectancy, decreased infant mortality, and acute illness related to childhood disease shifting toward chronic lifestyle diseases such as obesity and diabetes (Dye, 2008).…”
Section: Urbanization and Technification: A Detrimental Confluencementioning
confidence: 99%
“…A US study by Merikangas and colleagues (2010) showed that 22.2% of 13-18 year olds met the clinical assessment criteria for severe impairment or distress (anxiety 31.9%, behavioural disorders 19.1%, mood disorders 14%). Adding further concern, Canadians Flett and Hewitt (2013) showed that mental health issues were generally underestimated, citing lack of disclosure, as well as a range of existing sub-threshold conditions not quite meeting criteria for diagnoses. Over the last century, increased urbanization populations have experienced a general trend of increased life expectancy, decreased infant mortality, and acute illness related to childhood disease shifting toward chronic lifestyle diseases such as obesity and diabetes (Dye, 2008).…”
Section: Urbanization and Technification: A Detrimental Confluencementioning
confidence: 99%
“…Schools have a pivotal role in providing preventive mental health services (Flett & Hewitt, 2013;Leschied, Flett, & Saklofske, 2013). For example, in Canada, school-based mental health programs (e.g., the School-Based Pathway to Care model and the Innovative Psychology School Mental Health Initiative) proactively address students' mental health issues through collaboration between educators, students/families, and mental health service providers (Kutcher & Wei, 2013;Millar, Lean, Sweet, Moraes, & Nelson, 2013).…”
mentioning
confidence: 99%
“…Na literatura, são poucos os estudos voltados para a temática de problemas de internalização, reconhecidamente sub identificados e sub tratados, em que pese seu impacto adverso no desenvolvimento socioemocional e na saúde (Flett & Hewitt, 2013;Ghandour, Kogan, Blumberg & Perry, 2010). Nesse sentido, a identificação de tais problemas na infância, mesmo os subclínicos, é importante porque esses podem, com o tempo, transformar-se na forma completa do transtorno com o qual seus sintomas se relacionam, seja de ansiedade, depressão, ou ambos, em comorbidade (Dozois & Dobson, 2004;Flett & Hewitt, 2013).…”
unclassified